Self-Reported Dental Health Perception, its Consequences and Utilization of Oral Health Services among School Going Adolescent Girls in a Selective School of Dhaka Mohanagar: A Cross-Sectional Study - Ahmed, Anam; Sharmin, Salma; Lucky, Jesmin Sultana; Jahan, Md Shahed; Mannan, Huda; Tabassum, Faiza; Yeasmin, Momota (Journal of Dentistry and Allied Science, 2025)
Background: Oral health is an essential part of overall health and quality of life. The aim of the study was to assess the self-reported perception of dental condition, its consequences and utilization of oral health services among school girls in a selective secondary school of Dhaka Mohanagar. Methods: This cross-sectional study was carried out among 155 adolescents’ girls aged between 15 to 18 years at Siddheswari Girls’ High School, Dhaka in December 2023 using a convenient sampling method. After obtaining informed written consent from participants, data were collected through face-to-face interview using a pretested semi-structured questionnaire (Bengali language) regarding sociodemographic characteristics, self-perception of dental health condition & its consequences and utilization of oral health services. Collected data were edited and analyzed using IBM Statistical Package for the Social Sciences (SPSS) software version 27. Descriptive statistics presented by frequency, percentages, mean, standard deviation and bivariate analysis was done by Chi-square test (level of significance <.05). Results: The sample comprised adolescents’ girl aged 15 to 18 years (M = 17.03, SD = 1.12, 95% CI [16.85, 17.21]). A majority of the students (68.4%) were in the 17-18 age group, while 31.6% were 15-16 years old. Regarding educational status, nearly half of the students (49.7%) were in 10th grade and all were belonged from (89.7%) Muslim and (92.3%) nuclear families. Moreover, the most of students mentioned their monthly family’s income (49.68%) reported income between 30,000 and 49,999 Taka. Regarding self-reported perceived dental condition (table 2), the majority of students reported their teeth to be in average (45.2%) or good (40.6%) condition. In addition, most of girls rated their gum condition as good (45.8%) or average (40.6%). Whereas, the most prevalent consequence was dental sensitivity and pain (56.4%) often, and 21.3% reported it sometimes and gum bleeding during tooth brushing was reported as occurring sometimes by 47.8% and often by 13.0%. Most of students (70.3%) reported never visited to dentist. For the 46 students who had visited a dentist, the most common reason was for dental fillings (47.8%), followed by scaling (26.1%) and tooth extraction (21.7%). Alarmingly, only 14.8% of students reported having access to such programs, while the vast majority (85.2%) did not. There is statistically signification association found between age with last visit to dentist (<.050), reason for receiving dental treatment (<.070), periodic oral health checkup by school authority (< .001); and class (< .001) & Monthly family income (<.001) with periodic oral health checkup by school authority. Conclusion: School authority should take necessary steps to promote oral health classrooms and enhance periodic school based oral health programs biannually for achieving optimal oral health. Journal of Dentistry and Allied Science, Vol. 7 No 2: 8-18